Multiple Decubitus Ulcers in Dm type II Patients with Autologous Plasma-Rich Platelet therapy : A Case Report - Diani Nazma; Husnun Amalia; Lira Panduwaty; Antin Tri Laksmi; Christian Christian; Karlina Mahardieni; Karina Karina (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background:Multiple decubitus ulcers are a condition of injury that appears on several parts of the body’s skin due to pressure for a long time without any change in position. This condition usually occurs in someone with limited movement, for example, due to experiencing certain disease conditions that require the person to rest in bed for a long time, especially patients in the Intensive Care Unit (ICU) or after ICU care with chronic diseases and limited movement. Case Presentation: This case report assesses the success of multiple cases of decubitus ulcers in patients with type II diabetes mellitus with Autologous Plasma Rich Platelet therapy. Case report: Autologous PRP therapy is given by intralesional injection; debridement is done every three days and assessed every one week. Patients are also subjected to blood sugar control, blood pressure control, blood correction, and albumin to speed up the wound healing process in multiple decubitus ulcers. Conclusion:the conclusion of this case report with additional management in the form of intralesional injection of autologous PRP performed on multiple decubitus ulcer patients with Diabetes Mellitus, which is rich in growth hormone, will greatly help the wound healing process.